Aspartate β-hydroxylase targeting in castration-resistant prostate cancer modulates the NOTCH/HIF1α/GSK3β crosstalk. (11th June 2020) - Barboro, Paola; Benelli, Roberto; Tosetti, Francesca; Costa, Delfina; Capaia, Matteo; Astigiano, Simonetta; Venè, Roberta; Poggi, Alessandro; Ferrari, Nicoletta
Abstract: Castration-resistant prostate cancer (CRPC) is an incurable stage of the disease. A multivariate principal component analysis on CRPC in vitro models identified aspartyl (asparaginyl) β hydrolase (ASPH) as the most relevant molecule associated with the CRPC phenotype. ASPH is overexpressed in various malignant neoplasms and catalyzes the hydroxylation of aspartyl and asparaginyl residues in the epidermal growth factor (EGF)-like domains of proteins like NOTCH receptors and ligands, enhancing cell motility, invasion and metastatic spread. Bioinformatics analyses of ASPH in prostate cancer (PCa) and CRPC datasets indicate that ASPH gene alterations have prognostic value both in PCa and CRPC patients. In CRPC cells, inhibition of ASPH expression obtained through specific small interfering RNA or culturing cells in hypoxic conditions, reduced cell proliferation, invasion and cyclin D1 expression through modulation of the NOTCH signaling. ASPH and HIF1α crosstalk, within a hydroxylation-regulated signaling pathway, might be transiently driven by the oxidative stress evidenced inside CRPC cells. In addition, increased phosphorylation of GSK3β by ASPH silencing demonstrates that ASPH regulates GSK3β activity inhibiting its interactions with upstream kinases. These findings demonstrate the critical involvement of ASPH in CRPC development and may represent an attractive molecular target for therapy. Abstract : ASPH overexpression is observed in several tumors and found associated with shortened survival. Here, we demonstrate that PCa progression relies on ASPH overexpression. Inhibition of ASPH expression significantly reduced cell proliferation and invasion providing the rationale for important therapeutic implications.